Serum β-hCG, AMH, TSH, and PRL Levels in Predicting the Outcome of Early Pregnancy 14 Days after Embryo Transfer: A Prospective Cohort Study - Fatemeh Davari Tanha; Azam Rasti; Hamideh Pakniat; Shohreh Salimi Setudeh; Amir Hosseini; Mohammad Amin Rahimian Ghohroodi (Advanced Biomedical Research)
Background: Pregnancy outcomes in assisted reproductive technology (ART) are influenced by the ability of the embryos to create a pregnancy and maternal factors such as hormone levels to maintain and develop the pregnancy. This study investigated the role of β-human chorionic gonadotropin (β-hCG), anti-mullerian hormone (AMH), thyroid-stimulating hormone (TSH), and prolactin (PRL) in predicting pregnancy outcomes and determined cutoff values in women undergoing ARTs. Materials and Methods: This prospective study included 153 women who underwent infertility treatment in the Department of Reproductive Medicine of the Yas Hospital, Tehran University of Medical Sciences (Tehran, Iran). Serum β-hCG level on day 14 after embryo transfer and serum AMH, TSH, and PRL were measured. Patients with β-hCG levels >25 mIU/ml were included in the study. Finally, any statistically significant relationships between these serum values and clinical pregnancy and live birth rate were investigated. To predict pregnancy outcomes with β-hCG levels, a receiver operating characteristic curve was used to estimate the β-hCG cutoff values. Results: Serum β-hCG levels were significantly higher in live-birth patients than in other patients. The β-hCG cutoff value for live births was 830 mIU/ml, with an AUC of 0.5920, sensitivity of 61.04%, and specificity of 56.58%. Serum AMH, TSH, and PRL levels did not show any significant results. Conclusions: Serum β-hCG levels on day 14 after embryo transfer can be used to predict the probability of live birth in patients undergoing infertility treatment.